Comparison of Coconut Coir, Rockwool, and Peat Cultivations for Tomato Production: Nutrient Balance, Plant Growth and Fruit Quality - Xiong, Jing; Tian, Yongqiang; Wang, Jingguo; Liu, Wei; Chen, Qing (Frontiers in Plant Science, 2017)
Rockwool and peat are two common substrates used worldwide in horticultural crop production. In recent years environmental and ecological concerns raised the demand for reducing the use of rockwool and peat. Although coconut coir has been increasingly used as an alternative to rockwool and peat, it is still needed to comprehensively evaluate the feasibility of coconut coir before widely used. To meet this need, coconut coir (CC), rockwool (RC) and peat-vermiculite (PVC) cultivations were used as tomato cultivation substrates to evaluate their effects on EC, pH and mineral ions in root-zone solution and drainage, nutrient uptake by crops, nutrient balance of cultivation system, plant growth and fruit quality. In general, CC significantly increased K and S uptake by crops, photosynthesis, individual fruit weight and total fruit yield compared to RC, and increased P and K uptake by crops and total fruit yield compared to PVC. Moreover, CC significantly increased organic acid of fruit in 1st truss compared to both RC and PVC. The uncredited nutrient was overally lower under CC than under RC and PVC (the lower, the better). For all substrates, the blossom-end rot of fruit increased gradually from 3rd to 13th trusses. The blossom-end rot of fruit was not significantly influenced by CC compared to RC or PVC, but was sginificantly decreased by PVC compared to RC. Our results infer that coconut coir was a potential substrate that could be widely used in tomato production. However, the inhibition of blossom-end rot was still a challenge when coconut coir was used as cultivation substrate for tomato.